Model Matematika Penanggulangan Pencemaran Udara - Eri Ranyusa Putri; muhammad subhan (Journal of Mathematics UNP, 2018)
Abstract-Air pollution is a change in the composition of substances in the air from normal conditions. An air is said to be polluted if a certain amount of substance that is in the air for a long period of time exceeds its safe limit. Substances that most influence the occurrence of air pollution are carbon monoxide produced by vehicles. The purpose of this research is to form a mathematical model, analyze mathematical models that have been obtained, and interpret the results of the analysis of the mathematical model. This research is a basic research, which starts from creating variables, parameters, and assumptions. Mathematical models for air pollution control are obtained by nonlinear differential equation systems. The results of the model analysis obtained a fixed point that is not stable, so that we can do air pollution prevention by the number of trees must be a lot of carbon dioxide produced from the process of hydroxyl oxidation and carbon monoxide produced by existing vehicles.